Granulocytapheresis with modified fluid gelatin versus high‐molecular‐weight hydroxyethyl starch: a matched‐pair analysis. Issue 2 (10th November 2016) - Dullinger, Katharina; Pamler, Irene; Brosig, Andreas; Mohrez, Morad; Hähnel, Viola; Offner, Robert; Dormann, Frauke; Becke, Christine; Holler, Ernst; Ahrens, Norbert
Abstract : BACKGROUND: Granulocyte apheresis requires a sedimentation agent. Usually, hydroxyethyl starch (HES) is administered to donors for this purpose and, as granulocyte concentrate (GC) ingredient, also to patients. Authorities recently recommended suspending market authorizations for starch‐containing products due to side effects. Therefore, we tested the efficacy of modified fluid gelatin (MFG, Gelafundin 4%) versus hetastarch (Hespan) for GC apheresis. STUDY DESIGN AND METHODS: This retrospective matched‐pair analysis compared MFG‐ and hetastarch‐derived GCs. Each group consisted of 15 unrelated male donors mobilized with dexamethasone and granulocyte–colony‐stimulating factor for apheresis on 1 or 2 days with the COBE Spectra's PMN program. RESULTS: In each group, 24 GCs were collected from 15 male donors and analyzed. None of the HES‐derived products, but two of the MFG‐derived products (8.3%), had aggregates and could not be used. The HES‐derived products had significantly higher neutrophil counts on the first day (7.7 × 10 10 /unit vs. 4.0 × 10 10 /unit; p = 0.00005) as well as second day of apheresis (4.0 × 10 10 /unit vs. 1.1 × 10 10 /unit; p = 0.0002). Median white blood cell collection efficacies were lower with MFG than with HES on Day 1 (24% vs. 43%) and Day 2 (15% vs. 37%). Twenty‐one percent of the MFG‐derived products had less than 1 × 10 10 granulocytes. CONCLUSION: These results indicate that granulocyte apheresis is feasible with MFG as well as with hetastarch and that the latter is superior for GC production, if used in the same dosage. In addition, aggregates in GC from the COBE Spectra were observed in the MFG group but not in the hetastarch group.